Synthesis and Biological Activity of Piperazine Derivatives of Phenothiazine - Amani, A. M. (Drug Research, 2015)
Some novel piperazine derivatives of phenothiazine were synthesized. The structures of the synthesized compounds were characterized by elemental analysis, FT-IR, 1H- and 13C-NMR and Mass Spectroscopy. The compounds were evaluated for antibacterial, antifungal and antitubercular activity by cup plate, disc diffusion and Lowenstein-Jensen medium methods respectively. All the compounds showed good antibacterial activity against Staphylococcus aureus and Bacillus subtilis. Compound V showed equipotent antibacterial activity with streptomycin standard and showed better antibacterial activity against gram positive bacteria profile than gram negative bacteria. Zone of inhibition was not found for the compounds against Escherichia coli and Pseudomonas aeruginosa. All the compounds exhibited good antifungal activity against Aspergillus species and no activity against Candida albicans. All the compounds at a concentration of 100, 10 and 1 µg/L showed inhibition against the growth of Mycobacterium tuberculosis.
Keywords: phenothiazine derivatives; antibacterial; antifungal; antitubercular